Elizabeth Buettner, Europe after Empire. Decolonization, Society, and Culture - Oostindie, Gert (BMGN - Low Countries Historical Review, 2017)
Elizabeth Buettner, Europe after Empire. Decolonization, Society, and Culture. (Cambridge: Cambridge University Press, 2016, xii + 551 pp., isbn 9780 521131889)